2020
DOI: 10.1002/er.6264
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multi‐fuel combustion behavior and synergy effect using improved steady‐state discrete particle model simulation

Abstract: SummaryThis paper presents a simulation study of municipal solid waste (MSW) combustion using a multi‐fuel combustion model, which was an extended version from the one previously developed by the authors. The model was a steady‐state model with partial transient implementation as user‐defined functions (UDF) developed in ANSYS Fluent platform to investigate the combustion behavior of fuel interacting in the solid and gas phases. The solid phase was simulated using discrete particle model (DPM). The extended si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was found that the pyrolysis/gas oxidation reaction has a comprehensive dissipation effect on turbulence. The pyrolysis process is also used as a pre-step of the gasification or combustion processor as the input of volatile gases [103,116].…”
Section: Pyrolysismentioning
confidence: 99%
“…It was found that the pyrolysis/gas oxidation reaction has a comprehensive dissipation effect on turbulence. The pyrolysis process is also used as a pre-step of the gasification or combustion processor as the input of volatile gases [103,116].…”
Section: Pyrolysismentioning
confidence: 99%